Building active internet portals for document sharing using association rules. (1st September 2004) - Wong, Jacqueline; Du, Timon; Li, Honglei
An internet portal provides a simple way of putting popular web functions together. It is common for an individual to group his/her preferred websites into a personal portal. However, a user normally relies on search engines to look for information so a significant amount of time is often spent on searching the internet. This paper describes a form of push technology that automatically delivers documents to the personal internet portal. The association rules of data mining techniques are used to discover the relationships between documents so that the right document can be delivered to the right person.